2022
DOI: 10.3389/fmicb.2022.869661
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microfungi in a High Radon Cave Ecosystem

Abstract: Castañar Cave is a clear example of an oligotrophic ecosystem with high hygrothermal stability both seasonal and interannual and the particularity of registering extraordinary levels of environmental radiation. These environmental conditions make the cave an ideal laboratory to evaluate both the responses of the subterranean environment to sudden changes in the matter and energy fluxes with the exterior and also any impact derived from its use as a tourist resource under a very restrictive access regime. In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
2
10
0
Order By: Relevance
“…The history of samplings in Castañar Cave shows that only three fungi retrieved in the first fungal outbreak in 2008 were also found in the following 2009 and 2020 campaigns, as well as during the second outbreak in 2021: N. solani , F. oxysporum , and M. alpina [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The history of samplings in Castañar Cave shows that only three fungi retrieved in the first fungal outbreak in 2008 were also found in the following 2009 and 2020 campaigns, as well as during the second outbreak in 2021: N. solani , F. oxysporum , and M. alpina [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, we stated that N. solani was a permanent dweller of Castañar Cave because this fungus was present in all samplings since 2008 [ 17 ]. Some studies confirmed that this is a widespread fungus in nature and is considered a natural dweller in caves and subterranean environments [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently occurring species are common in caves. Aureobasidium pullulans is an endophytic fungus common in various caves [ 50 , 52 ], including ice and volcanic caves, and is a primary colonizer of oligotrophic environments [ 53 , 54 ]. A. niger may exhibit keratinolytic activity [ 55 ], and Alternaria alternata may have lignolytic potency [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal taxa so far recognized in caves are those commonly found on the Earth’s surface, and air currents entering and circulating within caves can distribute spores from the outside environment. It has also been suggested that the presence of fungi in caves is an indirect consequence of the entry of organic matter vehicled by cave animals, human visitors, and airborne spores from outside ( Martin-Pozas et al, 2022 ). Fungi are not distributed evenly throughout caves, being commonly associated with organic debris and cave fauna.…”
Section: Microbial Diversity In Cavesmentioning
confidence: 99%